EL IMPACTO DE PRODUCTOS VETERINARIOS SOBRE INSECTOS COPRÓFAGOS: CONSECUENCIAS SOBRE LA DEGRADACIÓN DEL ESTIÉRCOL EN PASTIZALES - Lumaret, Jean Pierre; Martínez M., Imelda (Instituto de Ecología, A.C., 2005)
The overall purpose of this paper is to review the major and recent literature relating the secondary effects of the main veterinary products on non-target organisms. The role of soil organisms which degrade dung of animals (dung beetles and flies, earthworms, microorganisms) is underlined. Dung beetles in particular, as they dig small tunnels, inoculate the heart of pats with microorganisms as they carry spores of telluric fungi and microorganisms on their integument and consequently this stimulate the microbial activity. The faecal residues of some compounds cause metabolic disorders and eventually death of invertebrates that ingest or transcuticulally absorb them, with locally a disturbance of the functioning of pastures with alteration in the rate of degradation of dung. Faecal residues or metabolites of drugs belonging to the benzimidazole and levamisole/morantel groups are relatively harmless to dung fauna, on the contrary to other anthelmintics such as coumaphos, dichlorvos, phenothiazine, piperazine, synthetic pyrethoids, and most macrocyclic lactones which have been shown to be highly toxic for dung feeding insects (abamectin, ivermectin, eprinomectin, doramectin), among which moxidectin was the less toxic for dung beetles. To date, the detrimental impact upon non-target organisms has been considered acceptable in eradicating the parasites because of their economic importance to commercial livestock production. Some routine treatments with high effects upon cow pat fauna appear poorly compatible with sustainable pastureland ecology.